An inside view of Qawmi girls’ madrasa in Bangladesh: An anthropological study - Zaman, Fariha (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Social Science in Anthropology, 2022.